Pengaruh Karakteristik Dan Tipe Keputusan Inovasi Komoditas Jambu Biji (Psidium guajava) Di Desa Argosuko, Kecamatan Poncokusumo, Kabupaten Malang, Jawa Timur - Nasution, Nadwah Amelia; Edi Dwi Cahyono; Mas Ayu Ambayoen (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
Over several periods of time, farmers in the village have adopted guava commodity innovations due to fluctuating market prices. The guava plant has been adopted by farmers in Argosuko Village for approximately four years. The sustainability of guava innovation over the years is due to its advantages that can meet the needs of farmers. This research is important to conduct to see to what extent the innovation characteristics of guava commodities have advantages over their substitutes and how Argosuko farmers decide to replace the commodities they grow as additional income for farmers which will have an impact on increasing farmers' income to meet their living needs. Therefore, this study aims to: 1) Describe the innovation characteristics of guava commodities in Argosuko Village, 2) Describe innovation adoption, 3) Analyzing the influence of innovation characteristics on the level of adoption, 4) Analyzing the influence of optional innovation decisions on the level of adoption. The research data analysis methods used are descriptive statistics and PLS-SEM analysis in measuring the influence of innovation characteristics and optional innovation decision. The analysis test results show that the innovation characteristics that have a significant influence â‰¤ 0.05 on the level of innovation adoption are relative advantage, complexity, trialability and observability. Meanwhile, what does not have a significant effect on the level of adoption of guava innovation is suitability. And the type of optional innovation decision has a significant influence â‰¤ 0.05 on the level of adoption of guava innovation.